2017
DOI: 10.1089/cap.2016.0198
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response in Pediatric Anxiety Disorders: Results from the Child/Adolescent Anxiety Multimodal Study

Abstract: Pill placebo-related improvement occurs early in the course of treatment and both clinical factors and expectation predict this improvement. Additionally, probabilistic approaches may refine our understanding and prediction of pill placebo response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…First, despite the general similarity of studies and our use of Bayesian hierarchical modeling to address the influence of exchangeability assumptions, unobserved factors may still affect the likelihood of AEs described in this report. Second, just as placebo response has received considerable attention in pediatric mood and anxiety disorders, the impact of placebo-related AEs, which affects our ability to quantify medication-related AEs, may vary as a result of patient expectation, clinician-specific factors (eg, experience with the disorder under study, expertise in the clinical trial population) 62 or trial design (eg, capture of AEs). In this regard, by choosing to examine OCD and anxiety disorders (rather than major depressive disorder), we have selected conditions with lower placebo response rates, [62][63][64] which may minimize the influence of high placebo response on AE reporting.…”
Section: Discussionmentioning
confidence: 99%
“…First, despite the general similarity of studies and our use of Bayesian hierarchical modeling to address the influence of exchangeability assumptions, unobserved factors may still affect the likelihood of AEs described in this report. Second, just as placebo response has received considerable attention in pediatric mood and anxiety disorders, the impact of placebo-related AEs, which affects our ability to quantify medication-related AEs, may vary as a result of patient expectation, clinician-specific factors (eg, experience with the disorder under study, expertise in the clinical trial population) 62 or trial design (eg, capture of AEs). In this regard, by choosing to examine OCD and anxiety disorders (rather than major depressive disorder), we have selected conditions with lower placebo response rates, [62][63][64] which may minimize the influence of high placebo response on AE reporting.…”
Section: Discussionmentioning
confidence: 99%
“…4 One of the clinical trials was excluded because it did not focus on pediatric trichotillomania, but instead on pediatric anxiety disorders more generally. 5 However, this study did have interesting results regarding pill-placebo response in anxiety disorders in children, notably that there is a placebo response within the first four weeks of treatment, after which placebo did not appear to have long term effects, whereas active treatment continued to show improvement with time. 5 This initial review of the seven clinical trials reduced the number of prospective studies to two.…”
Section: Related Literaturementioning
confidence: 80%
“…Second, no longitudinal assessment was conducted. A previous study of children with anxiety disorder reported that the placebo effect of therapeutic expectation was exerted within 4 weeks after therapy, but was not observed four to 8 weeks after therapy [ 31 ]. Third, in the current study, because we conducted a secondary analysis of our previous randomized controlled study, the number of participants performing resonant breathing at home was small and the behavioral effects were not fully evaluated.…”
Section: Discussionmentioning
confidence: 99%